The perception of UiTM Kedah Students on the service quality of counter services at Unit Kewangan UiTM Kedah / Effi Effendi Mawardee...[et al.] - Mawardee, Effi Effendi; Noor Azhar, Mohd Nur Farhan; Saad, Hana; Zakaria, Rozainizawati; Mat Saad, Siti Normaziah (2010)
Service quality can be defined as the degree to which a service meets a customer’s needs or expectation. Service receivers may have different values and different grounds of assessment towards the same service or organization. Quality is more than a relationship between a customer and a service provider. The objective of this research is to study the Perception of Diploma in Public Administration Students towards the quality of Counter Services at Unit Kewangan UiTM Kedah. Besides, it is also to study the perception of service receiver towards knowledge and courtesy of employees and their ability to inspire trust and confidence by looking at assurance dimension. In this particular context, the importance of quality dimension is studied based on the following factors which are assurance, empathy, reliability, responsiveness, and tangible. However, this study only focuses on assurance dimension. Assurance refers to the knowledge and courtesy of employees and their ability to inspire trust and confidence. Thus, the researchers focus on Unit Kewangan of UiTM Merbok specifically to look into whether the services provided by the staff have achieved the service quality or not, as well as zero defect when providing the service to the service receivers.